2008
DOI: 10.1258/ijsa.2008.008067
|View full text |Cite
|
Sign up to set email alerts
|

Genital tract infections among HIV-infected pregnant women in Malawi, Tanzania and Zambia

Abstract: SummaryThe aim of this study was to compare the prevalence and factors associated with genital tract infections among HIV-infected pregnant women from African sites. Participants were recruited from Blantyre and Lilongwe, Malawi; Dar es Salaam, Tanzania; and Lusaka, Zambia. Genital tract infections were assessed at baseline. Of 2627 eligible women enrolled, 2292 were HIV-infected. Of these, 47.8% had bacterial vaginosis (BV), 22.4% had vaginal candidiasis, 18.8% had trichomoniasis, 8.5% had genital warts, 2.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 18 publications
(18 reference statements)
6
34
1
1
Order By: Relevance
“…However, a Canadian study reported a much lower prevalence of CT infection (0.6%) (21) . Our results regarding the prevalence of CT infection are consistent with the results from studies that were performed in Rio de Janeiro (2.2%) (22) , Europe (1%) (23) , and Africa (2.6%) (24) .…”
Section: Discussionsupporting
confidence: 91%
“…However, a Canadian study reported a much lower prevalence of CT infection (0.6%) (21) . Our results regarding the prevalence of CT infection are consistent with the results from studies that were performed in Rio de Janeiro (2.2%) (22) , Europe (1%) (23) , and Africa (2.6%) (24) .…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review found only 2 African studies of STIs among people already infected with HIV and one of them was among pregnant women [7,8,9]. Thus the majority of studies examining STI co-infections among people already infected with HIV were in Western Europe and North America, where prevalence, incidence and risk factors for STIs may differ in important ways from that of sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…1 In developing countries, patients with genital tract infections often bypass formal healthcare services and seek care in the informal sector. 2 Diverse studies performed, with the objective of establishing the frequency of the most common infectious agents for vaginitis, have shown varying results.…”
Section: Introductionmentioning
confidence: 99%